Acute mental stress and surgical performance. Issue 1 (27th September 2018) - Grantcharov, P D; Boillat, T; Elkabany, S; Wac, K; Rivas, H
Abstract: Background: Stress has been shown to impact adversely on multiple facets critical to optimal performance. Advancements in wearable technology can reduce barriers to observing stress during surgery. This study aimed to investigate the association between acute intraoperative mental stress and technical surgical performance. Methods: Continuous electrocardiogram data for a single attending surgeon were captured during surgical procedures to obtain heart rate variability (HRV) measures that were used as a proxy for acute mental stress. Two different measures were used: root mean square of successive differences (RMSSD) and standard deviation of RR intervals (SDNN). Technical surgical performance was assessed on the Operating Room Black Box® platform using the Generic Error Rating Tool (GERT). Both HRV recording and procedure video recording were time-stamped. Surgical procedures were fragmented to non-overlapping intervals of 1, 2 and 5 min, and subjected to data analysis. An event was defined as any deviation that caused injury to the patient or posed a risk of harm. Results: Rates of events were significantly higher (47–66 per cent higher) in the higher stress quantiles than in the lower stress quantiles for all measured interval lengths using both proxy measures for acute mental stress. The strongest association was observed using 1-min intervals with RMSSD as the HRV measure ( P < 0·001). Conclusion: There is an association between measures of acute mental stress and worse technical surgical performance. Further study will help delineate the interdependence of these variables and identify triggers for increased stress levels to improve surgical safety. Graphical Abstract: Stress has been shown to adversely impact multiple facets critical to optimal performance in numerous high-performance domains, but barriers have limited observations of this phenomenon in the operating theatre. Using novel wearable technology, this study investigated the relationship and associations between intraoperative acute mental stress and technical surgical performance. Stress reduces surgical performance